Comprehensive echocardiographic evaluation of the right heart in patients with pulmonary vascular diseases: the PVDOMICS experience. (7th June 2021) - Jellis, Christine L; Park, Margaret M; Abidov, Aiden; Borlaug, Barry A; Brittain, Evan L; Frantz, Robert; Hassoun, Paul M; Horn, Evelyn M; Jaber, Wael A; Jiwon, Kim; Karas, Maria G; Kwon, Deborah; et al.
Abstract: Aims: There is a wide spectrum of diseases associated with pulmonary hypertension, pulmonary vascular remodelling, and right ventricular dysfunction. The NIH-sponsored PVDOMICS network seeks to perform comprehensive clinical phenotyping and endophenotyping across these disorders to further evaluate and define pulmonary vascular disease. Methods and results: Echocardiography represents the primary non-invasive method to phenotype cardiac anatomy, function, and haemodynamics in these complex patients. However, comprehensive right heart evaluation requires the use of multiple echocardiographic parameters and optimized techniques to ensure optimal image acquisition. The PVDOMICS echo protocol outlines the best practice approach to echo phenotypic assessment of the right heart/pulmonary artery unit. Conclusion: Novel workflow processes, methods for quality control, data for feasibility of measurements, and reproducibility of right heart parameters derived from this study provide a benchmark frame of reference. Lessons learned from this protocol will serve as a best practice guide for echocardiographic image acquisition and analysis across the spectrum of right heart/pulmonary vascular disease.